Critical analysis of forensic cut-offs and legal thresholds: A coherent approach to inference and decision. (July 2018) - Biedermann, A.; Taroni, F.; Bozza, S.; Augsburger, M.; Aitken, C.G.G.
Highlights: We critically discuss the definition and use of cut-off values by forensic scientists. We expose inherent definitional and conceptual shortcomings of scientific cut-offs. We point out when and why such values are inappropriate (e.g., in toxicology). We argue that with likelihood ratios, shortcomings of cut-offs can be avoided. Abstract: In this paper we critically discuss the definition and use of cut-off values by forensic scientists, for example in forensic toxicology, and point out when and why such values – and ensuing categorical conclusions – are inappropriate concepts for helping recipients of expert information with their questions of interest. Broadly speaking, a cut-off is a particular value of results of analyses of a target substance (e.g., a toxic substance or one of its metabolites in biological sample from a person of interest), defined in a way such as to enable scientists to suggest conclusions regarding the condition of the person of interest. The extent to which cut-offs can be reliably defined and used is not unanimously agreed within the forensic science community, though many practitioners – especially in operational laboratories – rely on cut-offs for reasons such as ease of use and simplicity. In our analysis, we challenge this practice by arguing that choices made for convenience should not be to the detriment of balance and coherence. To illustrate our discussion, we will choose the example of alcohol markers in hair, used widely by forensic toxicologists to reach conclusions regarding the drinking behaviour of individuals. Using real data from one of the co-authors' own work and recommendations of cut-offs published by relevant professional organisations, we will point out in what sense cut-offs are incompatible with current evaluative guidelines (e.g., [31] ) and show how to proceed logically without cut-offs by using a standard measure for evidential value. Our conclusions run counter to much current practice, but are inevitable given the inherent definitional and conceptual shortcomings of scientific cut-offs. We will also point out the difference between scientific cut-offs and legal thresholds and argue that the latter – but not the former – are justifiable and can be dealt with in logical evaluative procedures.